MICROBIOME BIODIVERSITY OF SOYBEAN RHIZOSPHERE UNDER APPLICATION OF FUNGICIDES AND INOCULATION BY MICROBIAL BIOFORMULATION ECOVIT - Г. О. Іутинська; Л. В. Титова; О. Г. Пінаєв; Є. Є. Андронов; С. В. Вознюк (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2017)
Biodiversity of soil microorganisms in the agroecosystems plays the major role for stabilization and conservation of soil fertility, increasing plants productivity. Aim. To study the diversity of microbiome phylums of the dark-grey podzolic soil in the soybean rhizosphere, the seeds treated by fungicides with following inoculation with the complex microbial bioformulation Ecovital. Methods. Molecular-biological methods, pyrosequencing of PCR-amplicons of 16S rRNA gene V-4 region. Results. In soybean rhizosphere microbiome, there were identified 20 phylums, 28 classes and 44 orders of Bacteria, and one phylum, one class and two orders of Archaea. The representation of Proteobacteria phylum has increased from 26.2% in the control sample to 35.8–37.6% in the samples with the application of fungicides and inoculation, Bacteroidetes, Firmicutes and Acidobacteria phylums has increased from 1.5%, 2.1% and 11% in the control sample to 3.5–5.4%, 2.6–4.7% and 12.8–13.3% in all researched samples, respectively. The increase of biodiversity indices (Shannon’s and Menhinik’s indices) and the decrease of dominance indices (Simpson’s and Berger-Parker’s indices) indicate the increase of biodiversity for the samples with application of complex inoculant Ecovital and fungicides with Ecovital. Conclusions. Complex inoculation and its combined use with fungicides have promoted the increase of prokaryotes biodiversity in soybean rhizosphere.